Deskrypcja długości i szerokości stóp kobiet i mężczyzn w obciążeniu masą własną, w wieku od 4 do 18 lat w świetle mory projekcyjnej - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław. Deskrypcja długości i szerokości stóp kobiet i mężczyzn w obciążeniu masą własną, w wieku od 4 do 18 lat w świetle mory projekcyjnej = Description the length and the width of the feet of men and women in the load weight of their own, ranging in age from 4 to 18 years in light of the moire projection. Journal of Education, Health and Sport. 2015;5(9):293-304. ISSN 2391-8306. DOI10.5281/zenodo.30682 http://dx.doi.org/10.5281/zenodo.30682 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A293-304 https://pbn.nauka.gov.pl/works/622295 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 08.09.2015. Deskrypcja długości i szerokości stóp kobiet i mężczyzn w obciążeniu masą własną, w wieku od 4 do 18 lat w świetle mory projekcyjnej Description the length and the width of the feet of men and women in the load weight of their own, ranging in age from 4 to 18 years in light of the moire projection Mirosław Mrozkowiak Uniwersytet Kazimierza Wielkiego, Instytut Kultury Fizycznej, Bydgoszcz e-mail: magmar54@interia.pl, strona: http://wadypostawy.republika.pl Słowa kluczowe: długość i szerokość stopy. Streszczenie Wstęp. Długość i szerokość stopy to cechy, których przyśpieszony wzrost w okresie pokwitania pojawia się najwcześniej. U chłopców przypada na okres między 12,5 a13 r.ż., wg innych doniesień długość i szerokość stopy u chłopców wzrasta do 18 r.ż. Z wiekiem stopa zmienia się z szerokiej i krótkiej u noworodków, do pośredniej u dzieci starszych. Cel. Określenie przebiegu zmian średnich wartości długości i szerokości stóp, okresów gwałtownego wzrostu i spowolnienia przyrostu badanych parametrów w grupie dziewcząt i chłopców w wieku od 4 do 18 lat. Materiał i metodyka. Pomiarami długości i szerokości stóp objęto populację 9804 dziewcząt i 8699 chłopców w wieku od 4 do 18 lat, z losowo wybranych przedszkoli i szkół regionu warmińsko–mazurskiego. Do oceny wykorzystano stanowisko do komputerowej oceny postawy ciała, techniką mory projekcyjnej. Wyniki. Krzywa średnich wartości długości stóp obojga płci ma bardzo zbliżony przebieg do wykresu właściwej płci. Krzywa rozpoczyna się wartością P: 168,2, L:168,22 mm, kończy P: 238,0, L:233,3 mm. W 14 r.ż. występuje obniżenie wartości do P: 214,68, L:209,91 mm. Szerokość posiada wartość początkową P: 62,99, L:64,92 mm, końcową P: 90,8, L:90,18 mm. W 14 r.ż. występuje załamanie do wartości P: 81,82, L:82,39 mm. Wnioski 1. Przyrost długości i szerokości stóp populacji żeńskiej i męskiej od 4 do 18 r.ż. jest równomiernie intensywny, przy czym w 14 r.ż. następuje spowolnienie przyrostu wielkości badanych cech. 2. Przebieg zmian średnich wielkości długości i szerokości stopy w wieku od 4 do 18 lat regionu warmińsko – mazurskiego nie znajduje w pełni potwierdzenia w badaniach metodą podometryczną. Keywords: length and width of the foot. Summary Admission. The length and width of the foot are the characteristics which accelerated growth during puberty occurs at the earliest. Boys fall for a period of between 12.5 and 13 deposition, according to other reports the length and width of the foot in boys rises to 18 the age of deposition rate varies from a wide and short in newborns, to indirect in children. Aim. Determination of course change of the average values of the length and width of the foot, periods of rapid growth and slow growth of the test parameters in the Group of boys and girls aged from 4 to 18 years. Material and methods. The measurements of length and width of the foot covered the population 9804 girls and 8699 boys aged from 4 to 18 years of age, with a randomly selected kindergartens and schools in the region of Warmia-Mazury. To evaluate the position was used to evaluate computer posture, projection moire. The results. The curve of the average length of the foot of both sexes has a very similar process to the appropriate sex. The curve starts at the value of P: 168,2, L: 168,22 mm, d: 238,0, l: 14 mm 233,3 deposition occurs downgrading to the P: 214,68, L: 209,91 mm. Width of initial value P: 62,99, L: 64,92 mm, final P: 90,8, L: 90,18 mm 14 students at the breakdown occurs to the value of P: 81,82, L:82, 39 mm. Conclusions 1. Increase the length and width of the foot of the female and male populations from 4 to 18 deposition is intense, with evenly deposition growth decelerate 14 size tested characteristics. 2. the Process of change to medium sized length and width of the foot between the ages of 4 to 18 years old in the region of Warmia-Mazury is not fully confirmed in research by podometric method.